Soil tillage methods by years interaction for harvest index of maize (Zea mays L.) using additive main effects and multiplicative interaction model. (2nd January 2019) - Bocianowski, Jan; Nowosad, Kamila; Szulc, Piotr
ABSTRACT: The objective of this study was to assess soil tillage methods by years interaction for harvest index (HI) of maize ( Zea mays L.) grown in West Poland by the additive main effects and multiplicative interaction model. The study comprised four soil tillage methods, analysed in 12 years through field trials arranged in a randomised complete block design, with four replicates. HI of the tested soil tillage methods varied from 0.354 to 0.692 throughout the 12 years, with an average of 0.530. In the variance analysis, 57.06% of the total harvest index variation was explained by years, 2.39% by differences between soil tillage methods, and 8.71% by soil tillage methods by years interaction. HI is highly influenced by year factors. The method of reduced conventional tillage [autumn shallow ploughing (15 cm), cultivator with string roller in spring] was the most stable (additive main effects and multiplicative interaction stability value, ASV=0.410) for the HI values among studied soil tillage methods. This result confirms the opinion on the possibility of shallowing autumn ploughing in the cultivation of maize for grain.